Pengaruh Kewajaran Harga dan Perkembangan Harga terhadap Kepuasan Pelanggan Pembelian Sepeda Motor Yamaha Vixion pada Dealer Lautan Teduh di Purbolinggo - Arlin, Deni Vavi; Imantoro, Jati (Universitas Muhammadiyah Metro, 2021)
Based on the results of the pre-survey, what became a phenomenon in this study was that there were still customers who were dissatisfied with the fairness of prices and price developments at Lautan Teduh Purbolinggo Dealers. In connection with these problems, the formulation of the problem in this study is